The double burden of malnutrition: Need for urgent policy action - Swaminathan, Soumya; Menon, Purnima (THG Publishing, 2020)
Last year was a remarkable one for nutrition in India. After years of slow and somewhat tentative action to acknowledge, understand and act on the challenge of undernutrition, India’s National Nutrition Mission brought focus and ambition and a range of actions followed. National and State governments were mobilised, district administrators engaged, the private sector mobilised in its own way, while civil society continued to push for accountability and action. As researchers committed to evidence-informed policies and programmes, we welcome India’s nutrition efforts. We call for even stronger systems to support the use of data and science to inform India’s efforts, to track progress and to learn from both successes and failures.